Transformasi Digital dalam Proses Operasional: Studi Kualitatif pada Bisnis Kuliner Berbasis Online - Nazla Sabirah; Nibi Nazwa Quinita Tanjung; Salsabila Rahma; Arsyadona Arsyadona (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of information technology has driven culinary business operators to adapt through digital transformation. This study aims to describe the implementation of digital transformation in the operational processes of online-based culinary businesses in Medan City. Using a descriptive qualitative approach, data were obtained through in-depth interviews and direct observations of five online culinary business owners. The results indicate that these businesses utilize various digital platforms such as GoFood, GrabFood, ShopeeFood, WhatsApp Business, and social media for daily operations, promotions, and customer services. Digital transformation has proven to improve operational efficiency and expand market reach, although it still faces challenges such as limited digital literacy and software costs. This study recommends the need for digital literacy training, strengthening of internet infrastructure, the development of local digital platforms, and further research on the impact of digital transformation on the performance of online culinary businesses.